Développement des exercices de Grammaire Introductif comme le jeu avec l’application de Wordwall - Maesaroh; Fitrasih, Ria (Universitas Negeri Semarang, 2025)
In French language learning, it is necessary to understand the elements and rules of grammar managed by the grammatical system. This research proposes to create introductory grammar exercises in game form using the Wordwall application and then develop the media to become reference material for grammar learning. This research used the R&D approach, which divides the process into five steps: researchers develop products through potential and problem analysis, data collection, product design, product validation, and product revision. The object of this research is students of the first semester of 2023, Department of French Language, Universitas Negeri Semarang. This study produced the results of three exercises: the repetition, the blank, and the structural exercises. Before creating these three exercises, the researcher did some needs analysis on the 39 first-semester students by distributing and collecting the questionnaire, with the result of 97.3% that the students need the repetition exercise and 92.3% that they need the blank exercises and the structural exercise, and then the product is validated by experts.